AN INVESTIGATION INTO LOSS OF MEANING IN THE TRANSLATION PROCESS AS MANIFESTED IN THE VIETNAMESE VERSION OF THE WORLD IS FLAT BY THOMAS L. FRIEDMAN - Trần Thị Mai Lê (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis conducts a research on the loss of meaning in English - Vietnamese translation of an international best-selling book by Thomas L. Friedman, The World Is Flat. This paper is divided into five chapters. The analysis is made on a bilingual presentation of the translation - English is the source language and Vietnamese is the target language. Firstly, the researcher describes some common cases of loss of meaning that occur during the translation process from English to Vietnamese. Then the researcher finds and analyzes cases of loss of meaning caused by linguistic and non-linguistic features in Vietnamese version of The World Is Flat. And the last is finding the ways that translators attempt to compensate for what might be seen as lost. The findings, it is hoped, will contribute to the research, the practice, the teaching and studying of Vietnamese - English translation.